Scaling-up integrated type-2 diabetes and hypertension care in Cambodia: what are the barriers to health system performance? - Chham, Savina; Van Olmen, Josefien; Van Damme, Wim; Chhim, Srean; Buffel, Veerle; Wouters, Edwin; Ir, Por (Frontiers in Public Health, 2023)
Background Non-communicable diseases (NCDs) such as type-2 diabetes (T2D) and hypertension (HTN) pose a massive burden on health systems, especially in low- and middle-income countries. In Cambodia, to tackle this issue, the government and partners have introduced several limited interventions to ensure service availability. However, scaling-up these health system interventions is needed to ensure universal supply and access to NCDs care for Cambodians. This study aims to explore the macro-level barriers of the health system that have impeded the scaling-up of integrated T2D and HTN care in Cambodia. Methods Using qualitative research design comprised an articulation between (i) semi-structured interviews (33 key informant interviews and 14 focus group discussions), (ii) a review of the National Strategic Plan and policy documents related to NCD/T2D/HTN care using qualitative document analysis, and (iii) direct field observation to gain an overview into health system factors. We used a health system dynamic framework to map macro-level barriers to the health system elements in thematic content analysis. Results Scaling-up the T2D and HTN care was impeded by the major macro-level barriers of the health system including weak leadership and governance, resource constraints (dominantly financial resources), and poor arrangement of the current health service delivery. These were the result of the complex interaction of the health system elements including the absence of a roadmap as a strategic plan for the NCD approach in health service delivery, limited government investment in NCDs, lack of collaboration between key actors, limited competency of healthcare workers due to insufficient training and lack of supporting resources, mis-match the demand and supply of medicine, and absence of local data to generate evidence-based for the decision-making. Conclusion The health system plays a vital role in responding to the disease burden through the implementation and scale-up of health system interventions. To respond to barriers across the entire health system and the inter-relatedness of each element, and to gear toward the outcome and goals of the health system for a (cost-)effective scale-up of integrated T2D and HTN care, key strategic priorities are: (1) Cultivating leadership and governance, (2) Revitalizing the health service delivery, (3) Addressing resource constraints, and (4) Renovating the social protection schemes.